A Drug Combination Screen Identifies Drugs Active against Amoxicillin-Induced Round Bodies of In Vitro Borrelia burgdorferi Persisters from an FDA Drug Library - Feng, Jie; Shi, Wanliang; Zhang, Shuo; Sullivan, David; Auwaerter, Paul G.; Zhang, Ying (Frontiers in Microbiology, 2016)
Although currently recommended antibiotics for Lyme disease such as doxycycline or amoxicillin cure the majority of the patients, about 10-20% of patients treated for Lyme disease may experience lingering symptoms including fatigue, pain, or joint and muscle aches. Under stress conditions such as starvation or antibiotic exposure, Borrelia burgdorferi can develop round body forms, which are a type of persister bacteria that are not killed by current Lyme antibiotics. To identify more effective drugs that are active against the round bodies of B. burgdorferi, we established a round body persister model induced by amoxicillin and screened the Food and Drug Administration (FDA) drug library consisting of 1581 drug compounds and also 22 drug combinations using the SYBR Green I/propidium iodide (PI) viability assay. We identified 23 drug candidates that have higher activity against the round bodies of B. burgdorferi than either amoxicillin or doxycycline. Eleven of these scored better than metronidazole and tinidazole which have been previously described to be active against round bodies. While some drug candidates such as daptomycin and clofazimine overlapped with a previous screen against stationary phase B. burgdorferi persisters, additional drug candidates active against round bodies we identified include artemisinin, ciprofloxacin, nifuroxime, fosfomycin, chlortetracycline, sulfacetamide, sulfamethoxypyridazine and sulfathiozole. Two triple drug combinations had the highest activity against round bodies and stationary phase B. burgdorferi persisters: artemisinin/cefoperazone/doxycycline and sulfachlorpyridazine/daptomycin/doxycycline. These findings confirm and extend previous findings that certain drug combinations have superior activity against B. burgdorferi persisters in vitro, even if pre-treated with amoxicillin. These findings may have implications for improved treatment of Lyme disease.